(untitled) (The Research of Medical Science Review, 2025)
Background: It is easy for clinicians to find thyroid nodules and yet many parathyroid conditions like primary hyperparathyroidism may occur together, making treatment more involved. Because both the thyroid and parathyroid glands are close to one another, surgical problems and confusing diagnoses are more common, so experts from different fields are needed for the most favorable outcomes. Objectives: To evaluate the surgical outcomes and identify perioperative challenges in patients presenting with thyroid nodules concurrently diagnosed with parathyroid disorders, and to determine the impact on complication rates and operative strategies. Study Design: A Retrospective Cross-Sectional Study. Place and duration of study: From 01 October 2024 to 31 March 2025, General Surgery Department, Sandeman Provincial Hospital / Bolan Medical Complex Hospital, Quetta. Methods: We performed a retrospective observational study on patients having thyroid nodule surgery with parathyroid disorders at a tertiary care center from 01 October 2024 to 31 March 2025, Information was gathered on patient demographics, the ways they presented clinically, imaging reports, findings during surgery, histopathology results and complications. People with only a problem in the thyroid or parathyroid were not included in the study. Surgery results and surgical approaches were studied using SPSS version 24.0, with the line separating significance being p<0.05. Results: Among the 82 participants, concurrent parathyroid adenoma was seen in 36 (43.9%) and 46 (56.1%) had hyperplasia along with thyroid nodules. Patients in the study were 52.4 ± 11.6 years old on average. Most of the cohort or 72%, consisted of female patients. In most cases (64.6%), we did a total thyroidectomy with a focused parathyroidectomy. Total complication incidence was 17.1% and short periods of abnormally low calcium in the blood were seen the most. Operative time was found to be significantly longer with parathyroid hyperplasia (p=0.021). When Sestamibi scans and neck ultrasound were done before surgery, it was easier to pinpoint the tumor and less surgeries were needed again (p=0.008). Conclusion: When both thyroid and parathyroid disorders occur, surgeons face both anatomical and overlapping symptomatic problems. With correct preoperative identification, bespoke surgery planning and monitoring throughout the procedure, the risk of issues decreases. Assessing a child from several perspectives improves the results. Surgeons have to keep an eye out for other medical problems in patients who have hyperkalemia and thyroid nodules to manage them all properly at once.